2013
DOI: 10.1016/j.neulet.2013.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral deficits, abnormal corticosterone, and reduced prefrontal metabolites of adolescent rats subject to early life stress

Abstract: The present study investigated the effect of early life stress in adolescent rats on brain metabolites, serum corticosterone, and depressive-like behavior. A group of rats were subject to early life stress from postnatal day (PND) 1 to 14. A matched control group was studied. Behavioral tests, serum corticosterone and high-resolution proton magnetic resonance spectroscopy were conducted between PND 30 and 40. In this study, adolescent rats exposed to early life stress demonstrated depressive-like behavior and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
(50 reference statements)
3
10
0
Order By: Relevance
“…Similar behaviour has also been reported in adult NH offspring (Pryce et al, 2001;Shalev & Kafkafi, 2002;Madruga et al, 2006). Further, exposure to LMS (3 h) or early deprivation may result in reduced reward behaviour such as reduced preferences for sweet solutions (Hui et al, 2011;Zhang et al, 2013a), although findings of no difference or increase have also been reported (Mourlon et al, 2010;Uchida et al, 2010;Oines et al, 2012;Zhang et al, 2013b). Since rats usually prefer drinking sweet solutions to water, the reduced preference for sucrose is interpreted as a loss of interest in pleasure, hence resembling the human state of anhedonia.…”
Section: Affective-like Behaviour In Animal Modelssupporting
confidence: 61%
“…Similar behaviour has also been reported in adult NH offspring (Pryce et al, 2001;Shalev & Kafkafi, 2002;Madruga et al, 2006). Further, exposure to LMS (3 h) or early deprivation may result in reduced reward behaviour such as reduced preferences for sweet solutions (Hui et al, 2011;Zhang et al, 2013a), although findings of no difference or increase have also been reported (Mourlon et al, 2010;Uchida et al, 2010;Oines et al, 2012;Zhang et al, 2013b). Since rats usually prefer drinking sweet solutions to water, the reduced preference for sucrose is interpreted as a loss of interest in pleasure, hence resembling the human state of anhedonia.…”
Section: Affective-like Behaviour In Animal Modelssupporting
confidence: 61%
“…Accordingly, many neuropsychiatric disorders are associated with abnormalities in the HPA axis, with chronically elevated cortisol and reduced sensitivity to GC [20], suggesting stress may contribute to their development. Experiments in rats have shown that rats exposed to early life stress show elevated GCs as adults [21]. Similar observations have been made in human subjects who show chronically elevated GCs and altered stress response long after a traumatic event [17].…”
supporting
confidence: 58%
“…Chronic stressors in early life result in permanent epigenetic, endocrine, neural, immune and inflammatory changes, constituting a relevant risk factor for several neuropsychiatric diseases in adult life (Xiong and Zhang, 2013 ; Zhang et al, 2013 ; Berens et al, 2017 ). Traumatic childhood experiences such as abuse, neglect and parental loss increase the incidence of psychiatric disorders, such as MD that boost to 59%–75% in adult life (Widom et al, 2007 ) and anxiety disorders that are 1.9–3.6-fold more common in people who experience early life stress (Fernandes and Osório, 2015 ).…”
Section: Discussionmentioning
confidence: 99%